Slow Ca2+ Efflux by Ca2+/H+ Exchange in Cardiac Mitochondria Is Modulated by Ca2+ Re-uptake via MCU, Extra-Mitochondrial pH, and H+ Pumping by FOF1-ATPase - Haumann, Johan; Camara, Amadou K. S.; Gadicherla, Ashish K.; Navarro, Christopher D.; Boelens, Age D.; Blomeyer, Christoph A.; Dash, Ranjan K.; Boswell, Michael R.; Kwok, Wai-Meng; Stowe, David F. (Frontiers in Physiology, 2019)
Mitochondrial (m) Ca2+ influx is largely dependent on membrane potential (ΔΨm), whereas mCa2+ efflux occurs primarily via Ca2+ ion exchangers. We probed the kinetics of Ca2+/H+ exchange (CHEm) in guinea pig cardiac muscle mitochondria. We tested if net mCa2+ flux is altered during matrix inward H+ leak that is dependent on matrix H+ pumping by ATPm hydrolysis at complex V (FOF1-ATPase). We measured [Ca2+]m, extra-matrix (e) [Ca2+]e, ΔΨm, pHm, pHe, NADH, respiration, ADP/ATP ratios, and total [ATP]m in the pres-ence or absence of protonophore dinitrophenol (DNP), mitochondrial uniporter (MCU) blocker Ru360, and complex V blocker oligomycin (OMN). We proposed that net slow influx/efflux of Ca2+ after adding DNP and CaCl2 is dependent on whether the ΔpHm gradient is/is not maintained by reciprocal outward H+ pumping by complex V. We found that adding CaCl2 enhanced DNP-induced increases in respiration and decreases in ΔΨm while [ATP]m decreased, ΔpHm gradient was maintained, and [Ca2+]m continued to increase slowly, indicating net mCa2+ influx via MCU. In contrast, with complex V blocked by OMN, adding DNP and CaCl2 caused larger declines in ΔΨm as well as a slow fall in pHm to near pHe while [Ca2+]m continued to decrease slowly, indicating net mCa2+ efflux in exchange for H+ influx (CHEm) until the ΔpHm gradient was abolished. The kinetics of slow mCa2+ efflux with slow H+ influx via CHEm was also observed at pHe 6.9 vs. 7.6 by the slow fall in pHm until ΔpHm was abolished; if Ca2+ reuptake via the MCU was also blocked, mCa2+ efflux via CHEm became more evident. Of the two components of the proton electrochemical gradi-ent, our results indicate that CHEm activity is driven largely by the ΔpHm chemical gradient with H+ leak, while mCa2+ entry via MCU depends largely on the charge gradient ΔΨm. A fall in ΔΨm with excess mCa2+ loading can occur during cardiac cell stress. Cardiac cell injury due to mCa2+ overload may be reduced by temporarily inhibiting FOF1-ATPase from pumping H+ due to ΔΨm depolarization. This action would prevent additional slow mCa2+ loading via MCU and permit activation of CHEm to mediate efflux of mCa2+.